Pengembangan Desa Wisata Berbasis Partisipasi Masyarakat Lokal di Desa Wanasari - Fitrianti, Arie; Yunani, Ahmad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The aims of the research are (1) to know rele and sinergity managerial localcommunity on tourism village know rele and sinergity managerial local communityon tourism village in Wanasari village (2) to know obstacles or problems ofcommunity on development tourism village in Wanasari village.This research does in Wanasari village, Sungai Loban district, Tanah Bumburegency. Technical collection data uses depth interviews and observational direct.Technical analysis data use descriptive qualitative with triangulation analysis.The result research show role of the community Wanasari village in planningthe development of tourism village are very greatly which like the community help tohelp clean culture tourism center and developing community like art or dance thencommunity too donation their money or some of plants or vas to tourism village, thenthe role of government and private sector has a significant effect because localgovernment has given funds to build infrastructure to tourism village and privatesector investment to support economic activity village.